E-Commerce Manufacturing and Management Training to Increase Production and Sales of Sirwal Pants at Al Waleed Moslem Shop - Dheni Apriantsani Budiman; Marjito; Rohmat Nur Ibrahim; Asep Ririh Riswaya; Heri Wahyudi; Dani Rohpandi; Ikbal Jamaludin; Susanto (Politeknik Mardira Indonesia, 2025)
Clothing entrepreneur partners today must be observant of the tastes and trends that are currently prevailing in society, besides that it is a challenge for entrepreneur partners to develop management, promotion and marketing that must be done. If you only rely on direct sales, of course, it must be supported by a variety of very good resources, such as a strategic location and an attractive spatial layout. Therefore, business partners need to penetrate into the form of online sales which of course requires various preparations that must be made, including by providing sufficient tools and human resources. Sirwal pants are one of the traditional clothing products that are currently quite popular among young people in the community. The opportunity to produce and market it is quite wide open, and the production process is relatively easy to do. To support the sales process progressively, of course, it is not enough to do it only by passive sales, but the online sales process must be carried out live within a certain period of time. The output of this activity is in the form of an account on an online sales application and the concept of live streaming or video sales applied to promotion and marketing by business partners.